Analisis Kebijakan Kepala Sekolah dalam Proses Pembelajaran Dimasa Pandemi Covid-19 - Hendri Yazid; Marjanis Marjanis; Nurhizrah Gistituati; Sufyarma Marsidin (Universitas Batanghari Jambi, 2021)
The principal is a school policy maker. During this Covid-19 pandemic, the Principal must think about how the education he leads is so that the teaching and learning process can run properly. This Research aims to find out how the Principal’s policies in implementing online learning for teachers and students during the COVID19 Pandemic. With the hope that students get quality education and can be achieved optimally. This research used a descriptive qualitative approach with field studies. The research's object was Madrasah Ibtidaiyyah Negeri 3 Padang, and the research subject is the principal and teachers. Data sources were obtained through observation, interviews, and documentation. The data analysis used was data reduction, data presentation, and verification. The results indicated that the principal of Madrasah Ibtidaiyyah Negeri 3 Padang had the policy to implement face-to-face learning and the number of students based on the health protocol. Principals, class-teachers, subject-teachers, and guardians of the students work together to make the policy successful.